Correlation of the use of corticosteroid in patients with COVID-19 and serum level of D-dimer - Al Ameri , Ali Mansoor Al Ameri (Karbala Journal of Medicine, 2022)
Abstract: The Global pandemic, COVID-19, represents a vigorous challenge for medical institutions because of unpredictable complications and the rapidity of spread. One of critical complications that is associated with COVID-19 insult is cardiovascular coagulopathy which can be fatal. This life threatening sequele could be prdected by estimation of serum level of D-dimer. The latter is a well known diagnostic marker of COVID-19 infection. Besides, D dimer is a fibrin metabolite and is directly related to the overall coagulation process in the body. Corticosteroid is the main stay of treatment of moderate and severe cases of COVID-19 infection especially those with considerable hypoxia. Aim of the study: to evaluate wheather using corticosteroid minimizes the occurrence of coagulopathy, an effect marked by reduction of the level of D-dimer during the course of the disease . Method: A total of 152 male patients infected with COVID-19 were selected randomly. They were diagnosed by a specialist Physicians according to standard guidelines. Patients were non-diabetic and non-hypertensive, 72 of them received dexamethasone for 5 days from the start of treatment of COVID-19. Serum level of D- dimer was estimated after seven days of starting of treatment then statistical analysis was done. Results: Data of the current study revealed that there was a significant reduction in the serum level of D-dimer in patients who received dexamethasone treatment as compared to the other group who didn't receive dexamethasone. Conclusion: It was concluded that using dexamethasone significantly decreases the serum level of D-dimer and thus may minimize the possibility of coagulopathy that induced as a result of COVID-19 infection. Keyword: D-dimer, COVID-19, dexameth asone